(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Influencer marketing is becoming increasingly popular in the trade sphere as an effective method of promoting goods and services. In this article, we focus on influencer collaboration techniques in trade marketing and their impact on consumer behavior. We discuss different strategies and approaches to partnering with influencers, as well as factors to consider when choosing additional partners to promote your products. With this, we bring to a similar situation and give recommendations for the effective use of influencer marketing in the trade sphere.